The Effect of Organic Fertilizer from Palm Factory Liquid Waste and NPK Fertilizer on Vegetative Growth of Peanuts (Arachis hypogaea L.) - Situmorang, Vickasyah Ramadani; Rahmadina, Rahmadina; Idris, M. (Jurnal Biologi Tropis, 2024)
Peanuts (Arachis hypogea L.) are leguminous plants which are classified as the most important nuts after soybeans in Indonesia. Indonesia not only imports rice but also imports other food crops such as peanuts. By using NPK fertilizer and organic liquid palm oil waste fertilizer as treatments in this study, we hope to boost the productivity of peanut plants. A Factorial Randomized Group Design (RAK) was employed in the study, with two treatment components, namely: 1. Factors for administering liquid organic fertilizer from palm oil mill waste (P) with 4 levels, namely: P0= POC LCPKS 0 ml/polybag P1= POC LCPKS 100 ml/polybag P2= POC LCPKS 200ml/polybag P3= POC LCPKS 300 ml/polybag, 2. The NPK (K) fertilizer application factor consists of: K0= 0 mg / polybag K1 = 7.5 mg/polybag K2 = 15 mg/polybag K3= 22.5 mg/polybag. The findings of the research indicate that the vegetative growth of peanut plants (Arachis hypogaea L.) is significantly impacted by the availability of a combination of organic fertilizer made from liquid palm oil waste and NPK fertilizer. Nearly every metric, including plant height, leaf area index, and blossom count, is significantly impacted by the application of a blend of NPK fertilizer and organic fertilizer made from liquid palm oil waste. The P3K2, P0K1, P1K3, and P2K1 levels represent the best level attained depending on the supply of POC from palm oil waste and NPK fertilizer.